SISTEM PENCEGAH KEBAKARAN PADA PERKEBUNAN JAMBU BIJI MENGGUNAKAN SENSOR SUHU LM35 DAN SMS GATEWAY BERBASIS ARDUINO UNO - Kelik Bayu Susatyo (Elkom : Jurnal Elektronika dan Komputer, 2019)
Guava is a fruit plant with various benefits for humans. Both the leaves and the fruit can be used to treat various diseases. As an example of the fruit to treat Dengue Hemorrhagic Fever, Tyfus, and so forth. The leaves can be used as traditional medicine to treat cough and diarrhea. In the highlands it is indeed cold and there is little possibility of plantation fires. However, fires can occur as a result of human activity both intentional and unintentional. The location of the plantation land that is relatively far from the residential population makes fires sometimes known too late. Therefore, it is necessary to create a tool to monitor the temperature and concentration of guava plantation smoke from a distance every day so that if the temperature or the density of smoke reaches a certain number that indicates the occurrence of fire then the tool will immediately send a notification via SMS to the plantation owner. In addition, the tool will immediately pour water from the reservoir or water reservoir into the guava plantation. In the water reservoir there is a tool to detect the volume of water. The device to be created uses the LM35 temperature sensor, MQ-2 smoke sensor, HC-SR04 Ultrasonic sensor, Relay, Arduino Uno R3 microcontroller and GPRS Shield along with the GSMSIM Card.